Esensi Kesalehan Sosial dalam Tradisi Halalbihalal di Indonesia - Salis Irvan Fuadi; Robingun Suyud El Syam (Journal of Creative Student Research, 2023)
This article attempts to reveal the essence of social piety in the halalbihalal tradition in Indonesia, by focusing on tracing what is done in that tradition so that it can be mapped where the form of social piety is. The article is a finding from qualitative research using a phenomenological approach. The results of the study show: that the halalbihalal tradition is an implementation of social piety, which functions as a complement to individual piety that has been forged before for one full month in the month of Ramadan. This refers to the hadith of the Prophet that sins against Allah can be forgiven directly by him, but sins related to other people must be lived by establishing direct communication with those concerned. Social piety in halal bihalal manifests in the act of apologizing, asking for halal, praying, and giving alms. The research implication, narrative understanding brings a bond of individual piety, and social piety is synergized in the personality of a Muslim so that he becomes a kaaffah Muslim. This research is expected to contribute to the conceptual of Islamic education.